2020
DOI: 10.21203/rs.3.rs-60301/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-time credible online health information inquiring: a novel search engine misinformation notifier extension (SEMiNExt) during COVID-19-like disease outbreak

Abstract: Public health-related misinformation spread rapidly in online networks, particularly, in social media during any disease outbreak. Misinformation of coronavirus disease 2019 (COVID-19) drug protocol or presentation of its treatment from untrusted sources have shown dramatic consequences on public health. Authorities are utilizing several surveillance tools to detect, and slow down the rapid misinformation spread online, still millions of misinformation are found online. However, there is no currently available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The present cross‐sectional study was conducted using an electronic researcher‐made questionnaire. This questionnaire was designed by reviewing related studies 1–3,5,7,8,12–14,20–27 and sample questionnaires related to security and privacy 15–18 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present cross‐sectional study was conducted using an electronic researcher‐made questionnaire. This questionnaire was designed by reviewing related studies 1–3,5,7,8,12–14,20–27 and sample questionnaires related to security and privacy 15–18 …”
Section: Methodsmentioning
confidence: 99%
“…The present cross-sectional study was conducted using an electronic researcher-made questionnaire. This questionnaire was designed by reviewing related studies [1][2][3]5,7,8,[12][13][14][20][21][22][23][24][25][26][27] and sample questionnaires related to security and privacy. [15][16][17][18] Also, the opinions of two medical informatics specialists and two software engineers with at least 5 years of experience in the information technology department of medical centers were used to design a questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To control and track the COVID-19 trajectory, different administrations have utilized modern artificial intelligence (AI) based methods integrated with 5G technology and aerial drone devices for real-time COVID-19 tracking [3] [4]. With no specific vaccine or medicine for preventing or curing [5], currently, the best approach to avoid COVID-19 is not to get ourselves exposed to it [6]. Social distancing must be preserved between all, as recent studies [7] have shown that even an asymptomatic person may silently propagate the disease without raising any suspicion.…”
Section: Introductionmentioning
confidence: 99%